Desain Mebel Denmark dalam Konteks Perkembangan Desain Kontemporer Skandinavia - Jamaludin Jamaludin; Imam Buchori; Imam Santosa (ITB Journal Publisher, LPPM ITB, 2007)
Denmark's strategic geographical position between Continental Europe and Scandinavian region makes them play a role as a bridge between both regions, including in the development of modern design. The development of Scandinavian furniture design influenced by proto-modern design movement in Europe such as Art and Craft Movement, De Stijl, Vienna School, Deutsche Werkbund, and also Bauhaus. The outer influences were accepted with critical understanding and blended with local character to produce a new design form known as Modern Scandinavia. Historically, the education of modern furniture design in Denmark and other Scandinavian countries pioneered by Kaare Klint (1888-1954) in the Royal Danish Academy of Fine Art, School of Architecture in Copenhagen. It was for the very first time, Klint arranged a systematic and comprehensive study about function, structure and furniture dimension based on British classics chair design. He also studied measurement of furniture based on the necessity of objects, which later known as Ergonomic. Klint's approach resulted in a functional aspect that lead to organic abstraction form by using natural wood as opposed to Bauhaus form concept that tended to use geometric abstraction form by using chrome-plated metal. Having described its historical roots, the study analyzed the characteristic of Denmark furniture design development that referring to (a) the values of craftsmanship, which is applied into modern design and manufacture process; (b) the commitment to natural material, which is used in furniture design, and (c) social idealism that applied in the society. Danish furniture designers' approach into modern design starts by reductionism that simplifies classical forms into basic-structural forms, and apply organic abstraction as opposed to Bauhaus's geometric abstractions.